2022
DOI: 10.22146/jsv.67400
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Perangkap Vavoua dan Nzi terhadap Keragaman dan Dinamika Populasi Stomoxys spp. pada Peternakan Sapi Perah di Pangalengan, Kabupaten Bandung

Abstract: Stomoxys spp. merupakan salah satu vektor penting penularan penyakit yang disebabkan oleh berbagai virus, bakteri dan heminth. Infestasi Stomoxys calcitrans pada sapi perah dapat meningkatkan kortisol, menyebabkan gangguan makan, kegelisahan, hingga berkurangnya bobot badan dan produksi susu. Perangkap Vavoua dan Nzi dapat digunakan sebagai perangkap Stomoxys spp. yang mengalami fluktuasi populasi sepanjang tahun pada musim tertentu dan dipengaruhi oleh iklim, suhu, kelembaban, intensitas cahaya serta adanya z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Another study of the diversity of the Stomoxys spp. at dairy cattle farms in Pangalengan, Bandung district, which was caught by using Vavoa and NZi traps every month, also showed that S. calcitrans was the dominant fly population (Kusumastuti et al 2022). The species Stomoxys caught in Bantul, and Kulon Progo were S. sitiens and S. indica.…”
Section: Discussionmentioning
confidence: 89%
“…Another study of the diversity of the Stomoxys spp. at dairy cattle farms in Pangalengan, Bandung district, which was caught by using Vavoa and NZi traps every month, also showed that S. calcitrans was the dominant fly population (Kusumastuti et al 2022). The species Stomoxys caught in Bantul, and Kulon Progo were S. sitiens and S. indica.…”
Section: Discussionmentioning
confidence: 89%